2018
DOI: 10.1039/c7ta10154f
|View full text |Cite
|
Sign up to set email alerts
|

MOF-derived Zn–Mn mixed oxides@carbon hollow disks with robust hierarchical structure for high-performance lithium-ion batteries

Abstract: A new hollow yet hierarchical MOF structure is developed to construct robust Zn–Mn oxides@carbon hybrids with excellent lithium-ion storage properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 58 publications
0
64
0
Order By: Relevance
“…Zhang et al synthesized carbon nanofiber@CoMn 2 O 4 composites, which displayed a high capacity of 870 mA h g −1 at 200 mA g −1 after 150 cycles . Wang et al reported that the Zn‐Mn mixed oxide@carbon hollow disks exhibited a reversible capacity of 547 mA g −1 at 2000 mA g −1 after 1000 cycles . These carbon composites not only buffer the volumetric expansion stress that occurs when TMOs react with Li + but also complement low electrical conductivity …”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al synthesized carbon nanofiber@CoMn 2 O 4 composites, which displayed a high capacity of 870 mA h g −1 at 200 mA g −1 after 150 cycles . Wang et al reported that the Zn‐Mn mixed oxide@carbon hollow disks exhibited a reversible capacity of 547 mA g −1 at 2000 mA g −1 after 1000 cycles . These carbon composites not only buffer the volumetric expansion stress that occurs when TMOs react with Li + but also complement low electrical conductivity …”
Section: Introductionmentioning
confidence: 99%
“…[13,36] The value of b was defined by the slope of plots of log (i)v ersus log (v). [35,[55][56][57] Moreover,t he proportion of the capacitive contribution can be obtained from Equations (17) and ( 18): [15,55] i ðVÞ¼k 1 vþk 2 v 1=2 ð17Þ It is worth mentioningt hat the value of b provides the basis for determining the energystoragem echanism of electrodes.…”
Section: Pseudocapacitive Contributionsmentioning
confidence: 99%
“…[1][2][3][4] Notably,M oS 2 ,w ith al arge surfacea rea and multiple active sites for the deposition of Li ions, is one of the most attractive 2D layered materials.I np articular, MoS 2 has an exceedingly typical SÀMoÀSs andwich structure, in whicht wo sulfur layers sandwichamolybdenum metal layer;t he atoms in the layers are connectedb ys trong covalentb onds, but the layers are bonded by relatively weak van der Waalsf orces. [13][14][15][16] For instance, Gong et al proposed that the introduction of as ingle metala tom could enhancet he lithium adsorptione nergy of materials and induce the uniform deposition of lithium,b ased on the lithium adsorption energy (1.92 eV) of the singlem etal atom (e.g.,N i, Co, Fe) being highert han that of the cohesive energy of the Li atom, which implied that the metal atoms could effectively induce the nucleation and deposition of lithium. In the different phases of MoS 2 ,t he stability of 1T-MoS 2 is worst, but with the best conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations